EFEKTIVITAS PEMASANGAN BERBAGAI MODEL PERANGKAP TIKUS TERHADAP KEBERHASILAN PENANGKAPAN TIKUS DI KELURAHAN BANGETAYU KULON KECAMATAN GENUK KOTA SEMARANG TAHUN 2014 (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2015)
Leptospirosis was a disease transmitted through rodent urine that had been infected with Leptospira bacteria with rat as primary transmission reservoir. One of controlling rat by mechanical was trapping. Different trap types had different effectiveness. The problem that arises was which trap model was most effectively applied to the success of a rat catcher in the Bangetayu Kulon Village. This type of research was quasi experimental by applying several models of rat traps. A purposive sampling was used in the research. The samples were 30 homes. From the results of the observation, there were 21 rats were caught using live trap with 14% trap success, 18 rats were caught using snap trap with 12% trap success, and 23 rats were caught using glue rat with 15.33% trap success. Based on the Kruskal-Wallis test results showed no difference between the model trap of live trap, snap traps, and glue traps to the successful model of catching rat (p-valeu=0,648 > Î±=0.05). Trap success in this area was high about 13.78%. Researcher recommends to do control the rats in the house reutine and continually with gleu rat trap and put the trap in the place that always be through by rats.